Arginine Metabolism and Cancer - Albaugh, Vance L. (J Surg Oncol, 2016)
Arginine is a conditionally essential amino acid that has been identified as an important player in a number of biologic processes, including normal function of the cardiovascular and immune systems. Countless studies have demonstrated that arginine is necessary for cellular growth and can become limiting in states of rapid growth like malignancy. Given this requirement for arginine in malignant cells, investigators have examined the potential for arginine deprivation therapy as an adjuvant treatment for cancers that are unable to synthesize arginine de novo. On the contrary, arginine has also been identified as being critically important for immune surveillance that also targets and destroys malignant cells. Thus, arginine has been paradoxically identified as being both necessary for cancer growth and normal immune function. A number of factors that include the type of cancer, expression of arginine synthetic genes, tumor microenvironment and host immune cell-cancer cell interactions can affect the progression of malignancy. In this manuscript, we review the data supporting arginine deprivation and supplementation in cancer therapies and the currently registered trials that are trying to understand which of these strategies might lead to advances in cancer therapies.